KEJAHATAN KESEHATAN DI ERA DIGITAL: TINJAUAN HUKUM PIDANA DAN PERDATA ATAS PENYALAHGUNAAN DATA PASIEN DAN TELEMEDISIN YANG TIDAK TERSTANDAR - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
The digitalisation of healthcare services in Indonesia has accelerated significantly since the COVID-19 pandemic, with telemedicine emerging as the primary solution for providing remote access to healthcare. This digital transformation has brought about innovations in healthcare delivery systems that have improved the quality of public services, but has also given rise to new risks of healthcare-related crime, such as the misuse of patient data and non-standardised telemedicine practices. This study employs a normative legal approach using a literature review method to analyse the forms of criminal and civil liability for these two legal issues. The findings indicate that the misuse of patient data constitutes a healthcare offence requiring a comprehensive criminal law approach based on Law No. 27 of 2022 on the Protection of Personal Data and the ITE Law, with criminal penalties of up to 8 years’ imprisonment and/or a fine of up to Rp800 million for unauthorised access. Unstandardised telemedicine gives rise to civil liability under Article 1365 of the Civil Code (unlawful acts) and Article 1243 of the Civil Code (breach of contract) when it results in misdiagnosis or inadequate treatment. The interconnection between criminal and civil aspects demonstrates that digital healthcare offences are complex crimes requiring dual law enforcement. Regulatory weaknesses are evident in the absence of technology legislation that explicitly governs telehealth and the lack of comprehensive data protection regulations. There is a need to strengthen regulations on telemedicine service standards, enhance the security of health data systems, oversee digital health platforms, and educate healthcare professionals and the public to reinforce the ecosystem of personal data protection and legal certainty in digital healthcare services.